Efeito do encruamento na cinética de nitretação dos aços inoxidáveis austeníticos - Martins, Eva Paganini (2010)
This paper deals with the effects of cold work on the nitriding kinetics and surface micro-hardness of the 3XX family of austenitic stainless steels. Nitriding is a thermo-chemical treatment based on the nitrogen diffusion and, under some specific circumstances, carbon in lower quantities, in to a ferrous matrix. The nitriding process improves particularly high cycle fatigue resistance, wear resistance, and corrosion resistance for carbon steels. To study the cold work effect on the material, samples of 304 and 316 were strained in tension tests to conventional deformation of 10%, 25% and up to rupture point prior to the nitriding process. A sample without deformation was kept for reference. It is possible to verify, based on the test performed, that the AISI 304 has smaller deformation capacity when compared to the 316 in terms of elongation on strain test presenting a higher degree of cold work deformation. Also the 304 presents a reduction on nitrided layer thickness and a smaller percentage of nitrogen in the nitrided layer after the cold work (difference of 1% point versus 0,5 for the 316) It is also possible to observe the smaller density on the 304 after the cold work which can be attributed, according to the literature, to the formation of cold work martensite during the cold work process.